Venezia, una città senza cavalli né automobili. Peggy Guggenheim House/Home - Mantese, Eleonora (Firenze Architettura, 2019)
This article analyses Peggy Guggenheim’s important role as a patron of the arts and the significance of her Venetian house in Ca’ Venier dei Leoni as an important fragment of the city. Peggy Guggenheim was well aware, after living a cosmopolitan life, of the reasons for choosing Venice as a haven both for her and for her art collection, which is open to the city. This article also analyses some of Peggy Guggenheim’s considerations regarding the city and the spaces of the house.